Do local conspecific density and floral display size influence fruit set via pollinator visitation in Orchis militaris?. (1st May 2019) - Henneresse, Thomas; Kaiser, Aurélien; Wesselingh, Renate A.; Tyteca, Daniel
Abstract : Plant density varies naturally, from isolated plants to clumped individuals, and this can influence pollinator foraging behaviour and plant reproductive success. In addition, the effect of conspecific density on reproduction may depend on the pollination system, and deceptive species differ from rewarding ones in this regard, a high density being often associated with low fruit set in deceptive plants. In our study, we aimed to determine how local conspecific density and floral display size (i.e. number of flowers per plant) affect fruit set in a deceptive orchid ( Orchis militaris ) through changes in pollinator visitation. We measured fruit set in a natural population and recorded pollinator abundance and foraging behaviour within plots of different O. militaris densities. Detailed data were recorded for the most abundant potential pollinators of O. militaris, i.e. solitary bees. Floral display size was negatively correlated to fruit set in medium‐density plots, but uncorrelated in low‐ and high‐density plots. Plot density had no effect on solitary bee abundance and visitation, which may be due to low pollinator abundance within the study site. The proportion of visited flowers per inflorescence was negatively influenced by floral display size, which is in line with previous studies. In addition, solitary bees spent decreasing time in successive flowers within an inflorescence, and the time spent per flower was negatively affected by ambient temperature. Our results suggest that pollinator behaviour during visitation is poorly linked to pollen deposition and reproductive success in O. militaris .